Bioactive and antioxidant properties in highbush blueberry cultivars: identifying superior cultivars for nutritional biofortification - Akbari, Azam; Xu, Yige; Wei, Xin; Liu, Zichen; Ergün, Doğan; Akgöl, Cihan; Dong, Feiyu; Ercişli, Sezai; Kafkas, Salih; Liu, Cheng; Kafkas, Nesibe Ebru (Frontiers in Plant Science, 2026)
IntroductionHighbush blueberries (Vaccinium corymbosum L.) are recognized as functional foods with exceptional health-promoting properties, yet comprehensive comparative evaluations of cultivar-dependent variation in bioactive compounds remain limited for breeding applications.MethodsThis study characterized phenolic profiles, anthocyanin content, sugar composition, and antioxidant capacity of 21 highbush blueberry cultivars (19 Southern Highbush, 2 Northern Highbush) grown under uniform conditions at Liaoning Institute of Pomology, China. Phenolic compounds were quantified by HPLC-DAD, sugars were analyzed by HPLC with refractive index detection, and antioxidant activity was assessed using DPPH radical scavenging assay. Data were analyzed using ANOVA, Pearson correlation, principal component analysis (PCA), and hierarchical cluster analysis.ResultsSignificant cultivar effects (p<0.001) were detected for all biochemical parameters. Total phenolic content exhibited 2.7-fold variation (253–688 mg GAE/100 g DW), with 'Misty', 'Twilight', and 'Unknown' showing highest values. Total anthocyanins varied 4.4-fold (603–2678 mg/100 g DW), with 'Eureka', 'Twilight', and 'Rossini' demonstrating superior accumulation. Eight major phenolic compounds were identified, with chlorogenic acid (61.44–223.89 mg/100 g DW) predominating among phenolic acids and malvidin-3-glucoside as the principal anthocyanin. Sugar profiling revealed glucose and fructose as predominant carbohydrates (92–97% of total sugars), with total sugar content ranging 2.9-fold (6.13–18.06 g/100 g DW). DPPH radical scavenging capacity ranged from 35.26% to 69.08%, strongly correlating with total phenolic content (r=0.73). PCA explained 50.1% of cumulative variance and differentiated cultivars into four distinct metabolic clusters: sugar-anthocyanin co-accumulators ('Rossini', 'Twilight'), superior antioxidant types ('Misty', 'Magnifica', 'Unknown'), gallic acid specialists ('Jewel', 'L503', 'Ventura'), and cyanidin-3-glucoside specialist ('Eureka').ConclusionThese findings reveal extensive genotypic diversity in primary and secondary metabolism among highbush blueberry cultivars, providing valuable germplasm resources and selection criteria for breeding programs aimed at developing elite cultivars with enhanced nutritional quality and superior antioxidant properties.